Propagation of spontaneously actuated pulsive vibration in human heart wall and in vivo viscoelasticity estimation - Kanai, H. (IEEE transactions on ultrasonics, ferroelectrics, and frequency control, 2005)
Though myocardial viscoelasticity is essential in the evaluation of heart diastolic properties, it has never been noninvasively measured in vivo. By the ultrasonic measurement of the myocardial motion, we have already found that some pulsive waves are spontaneously excited by aortic-valve closure (AVC) at end-systole (To). These waves may serve as an ideal source of the intrinsic heart sound caused by AVC. In this study, using a sparse sector scan, in which the beam directions are restricted to about 16, the pulsive waves were measured almost simultaneously at about 160 points set along the heart wall at a sufficiently high frame rate. The consecutive spatial phase distributions, obtained by the Fourier transform of the measured waves, clearly revealed wave propagation along the heart wall for the first time. The propagation time of the wave along the heart wall is very small (namely, several milliseconds) and cannot be measured by conventional equipment. Based on this phenomenon, we developed a means to measure the myocardial viscoelasticity in vivo. In this measurement, the phase velocity of the wave is determined for each frequency component. By comparing the dispersion of the phase velocity with the theoretical one of the Lamb wave (the plate flexural wave), which propagates along the viscoelastic plate (heart wall) immersed in blood, the instantaneous viscoelasticity is determined noninvasively. This is the first report of such noninvasive determination. In in vivo experiments applied to five healthy subjects, propagation of the pulsive wave was clearly visible in all subjects. For the 60-Hz component, the typical propagation speed rapidly decreased from 5 m/s just before the time of AVC (t = To - 8 ms) to 3 m/s at t = To + 10 ms. In the experiments, it was possible to determine the viscosity more precisely than the elasticity. The typical value of elasticity was about 24-30 kPa arid did not change around the time of AVC. The typical transient values of viscosity decreased rapidly from 400 Pa/spl middot/s at t = To - 8 ms to 70 Pa-s at t = To + 10 ms. The measured shear elasticity and viscosity in this study are comparable to those obtained for the human tissues using audio frequency in in vitro experiments reported in the literature.